2015
DOI: 10.1371/journal.pone.0129613
|View full text |Cite
|
Sign up to set email alerts
|

On Comparison of Series and Numerical Solutions for Flow of Eyring-Powell Fluid with Newtonian Heating And Internal Heat Generation/Absorption

Abstract: In this paper, we have investigated the combined effects of Newtonian heating and internal heat generation/absorption in the two-dimensional flow of Eyring-Powell fluid over a stretching surface. The governing non-linear analysis of partial differential equations is reduced into the ordinary differential equations using similarity transformations. The resulting problems are computed for both series and numerical solutions. Series solution is constructed using homotopy analysis method (HAM) whereas numerical so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…(20) reduces to the flow problem given by Grubka and Bobba. 30 Table V is constructed to compare the heat transfer rate for various values of Prandtl number Pr in a limited sense. An excellent agreement has been found which leads to conformity of present work.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(20) reduces to the flow problem given by Grubka and Bobba. 30 Table V is constructed to compare the heat transfer rate for various values of Prandtl number Pr in a limited sense. An excellent agreement has been found which leads to conformity of present work.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…The influence of mixed convection on Eyring-Powell nano fluid flow along a stretching sheet was addressed by Malik et al 28 Goswami et al 29 presented the flow of Eyring-Powell fluid in the presence of electroosmosis with interfacial slip effect. Hayat et al 30 discussed the both numerical and series solution of the Eyring-Powell fluid flow in the presence of internal heat generation/ absorption and Newtonian heating effects. The heat transfer along Eyring-Powell fluid flow with variable thermal conductivity was analyzed by Megahed.…”
Section: -2mentioning
confidence: 99%
“…Walters' B fluid provides the first order approximation to elasticity, and its low order elasticity reduces the flow instability. The Walters' B fluid model characterizes the polymeric liquids in biotechnology and chemical engineering …”
Section: Introductionmentioning
confidence: 99%
“…The radiation effects on free convection flow near a moving vertical plate with Newtonian heating was also studied by Narahari and Ishak . Hayat et al have made the comparison of series and numerical solutions for a flow of Eyring‐Powell fluid with Newtonian heating and internal heat generation/absorption. Khan et al investigated the hydromagnetic nonlinear thermally radiative nano‐liquid flow with Newtonian heat and mass conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The radiation effects on free convection flow near a moving vertical plate with Newtonian heating was also studied by Narahari and Ishak. 39 Hayat et al 40 The process of heat and mass transfer in porous media finds applications in many of engineering branches. In industrial applications it is found in glass fiber production, hot rolling and wire drawing, the extrusion of plastic sheets, glass blowing, and drawing plastic films under different heating processes.…”
Section: Introductionmentioning
confidence: 99%